The Relationship Between Physical Activity and Learning Outcomes For Upper Elementary School Students - Muhamad, Akmal; Dinangsit, Dinar; Rahman, Aam Ali (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to determine the relationship between physical activity and learning outcomes of upper-grade elementary school students. Physical activity is defined as body movements that require energy expenditure and is categorized into light, moderate and heavy activities. This study used a quantitative approach with a correlational design. The research sample amounted to 205 students in grades IV to VI who were selected by purposive sampling technique from several elementary schools. The instrument used to measure physical activity was the PAQ-C (Physical Activity Questionnaire for Children) questionnaire while learning outcomes were obtained from students' report cards. Significant between physical activity and learning outcomes with a correlation value of -0.181 and a significance of 0.009. This means that the higher the students' physical activity level, the lower their learning outcomes. This result contradicts some theories that physical activity improves cognitive function and academic achievement. However, this finding can be explained through time management factors and the high intensity of physical activity, which can cause fatigue and reduce study time. This study provides important implications for schools and parents to help students optimally balance physical activity and study time.